Cash Waqf Linked Deposit; Sebuah Alternatif Pendanaan Pendidikan Tinggi - Kurniawan, Eric; Maika, M. Roslianor; Latifah, Fitri Nur; Kristiyanto, Rahadi (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2024)
This research analyzes the potential of the IPB-BSI-01 Series Cash Waqf Linked Deposit (CWLD) in collecting waqf funds for education. Using a qualitative descriptive approach with interview techniques and documentation studies, it was found that the CWLD Series IPB-BSI-01 succeeded in attracting public interest, collecting more than IDR 19.5 billion in waqf funds. However, this number has only reached 19% of the national target of IDR 100 billion, indicating that there are still large opportunities for improvement. The success of the IPB-BSI-01 Series CWLD is due to the ease of access and flexibility of waqf, transparency and accountability in fund management, as well as the clear benefits of educational scholarships for recipients. Challenges faced include a lack of socialization and literacy of CWLD products in the community, as well as the gap between national targets and current funding. The research conclusion shows that the CWLD IPB-BSI-01 Series has great potential as an important instrument in collecting education waqf funds in Indonesia. Constructive steps that need to be taken include intensive outreach, optimizing technology, diversifying fundraising strategies, strengthening transparency and accountability, as well as developing innovative products and services. With the collaboration of various parties, including the government, educational institutions, the private sector and the wider community, the IPB-BSI-01 Series CWLD program can achieve national targets and provide a significant positive impact on the future of education in Indonesia.